Study the Effect Different Radioactive Dose on Mechanical Properties of Composite Material from Novolak Resin Exposure to High – Energy Radiation - Abbas, Rula Abdul Khider; Sahib, Muzher Ali; Hamza, Muhammad Slab (Al-Khwarizmi Engineering Journal, 2009)
The research involves using phenol – formaldehyde (Novolak) resin as matrix for making composite material, while glass fiber type (E) was used as reinforcing materials. The specimen of the composite material is reinforced with (60%) ratio of glass fiber. The impregnation method is used in test sample preparation, using molding by pressure presses. All samples were exposure to (Co60) gamma rays of an average energy (2.5)Mev. The total doses were (208, 312 and 728) KGy. The mechanical tests (bending, bending strength, shear force, impact strength and surface indentation) were performed on un irradiated and irradiate samples. All of the mechanical properties were improved with an increase in radioactive dose of up to (312) KGy to be decreased afterwards. The topography of some physically tested specimens was studied using optical microscopy.